High specificity of combined narrow band imaging and autofluorescence mucosal assessment of patients with head and neck cancer1. Issue 5 (28th June 2012) - Nguyen, Phan; Bashirzadeh, Farzad; Hodge, Robert; Agnew, Julie; Farah, Camile S.; Duhig, Edwina; Clarke, Belinda; Perry‐Keene, Joanna; Botros, David; Masters, Ian Brent; Fielding, David
Abstract Background The purpose of this study was to evaluate combined autofluorescence (AF) and narrow band imaging (NBI) for detection of mucosal lesions additional to known primary head and neck cancers and to determine impact on management. Methods Patients with head and neck cancer requiring preoperative screening or posttreatment surveillance had white light (WL), AF and NBI inspection of the head and neck and bronchus. Known primary cancers were not analyzed, only additional lesions. Moderate dysplasia or worse was considered significant. Results In all, 73 patients were recruited. Respectively, there were 24 and 18 additional lesions in the head and neck and bronchus that had significant histopathology. In both regions, AF and NBI were more sensitive than WL for detecting significant dysplasia with NBI demonstrating better specificity than AF (p = .003); 11 of 73 patients (15.1%) had additional findings detected by AF and NBI, which had an impact on management. Conclusion Combined AF and NBI inspection is highly specific at panendoscopy and can influence management. © 2012 Wiley Periodicals, Inc. Head Neck, 2013